2011
DOI: 10.1007/s11914-011-0077-9
|View full text |Cite
|
Sign up to set email alerts
|

Bone, Inflammation, and Inflammatory Bowel Disease

Abstract: Osteoporosis is a leading cause of morbidity in patients with inflammatory bowel disease (IBD). Bone loss is an early systemic process and occurs even before clinical disease manifests. Bone disease is attributed to vitamin D deficiency, steroid use, and/or systemic inflammation. In this review, we discuss the molecular pathways of bone loss mediated by inflammatory cytokines and other mediators. Further research will hopefully clarify the mechanisms of inflammation-induced bone loss in IBD and guide effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 59 publications
0
41
0
1
Order By: Relevance
“…multiple positive and negative receptors, the effect of IgGs varies among the different subtypes and the effect of monomeric and polymeric IgG also differs, it has been difficult to elucidate the molecular basis of IgG regulation of osteoclastogenesis despite the wealth of in vitro and in vivo observations of the involvement of FcgRs in bone metabolism 6,7,14,[6][7][8][9][10][11][12][13][14][15][16][17][18]28,29 . This study affords a detailed picture of the regulation of osteoclastogenesis by the IgG-FcgR system, in which both ligands and receptors are differentially regulated under physiological and pathological conditions, providing clear evidence for the IC-mediated regulation of bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…multiple positive and negative receptors, the effect of IgGs varies among the different subtypes and the effect of monomeric and polymeric IgG also differs, it has been difficult to elucidate the molecular basis of IgG regulation of osteoclastogenesis despite the wealth of in vitro and in vivo observations of the involvement of FcgRs in bone metabolism 6,7,14,[6][7][8][9][10][11][12][13][14][15][16][17][18]28,29 . This study affords a detailed picture of the regulation of osteoclastogenesis by the IgG-FcgR system, in which both ligands and receptors are differentially regulated under physiological and pathological conditions, providing clear evidence for the IC-mediated regulation of bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented that enhanced bone resorption is associated with the activation of the immune system observed in autoimmune or inflammatory diseases, such as rheumatoid arthritis (RA) 11 , systemic lupus erythematosus (SLE) 12 and inflammatory bowel disease 13 . The role of FcgRs has been explored in arthritis models [14][15][16][17][18] ; however, it has been difficult to observe their direct effects on bone metabolism due to their central contribution to the onset of autoimmune disease and inflammation.…”
mentioning
confidence: 99%
“…Bones are targets of inflammation, with inflammatory cytokines promoting bone resorption which results in systemic bone loss (30). A clear example of an infl ammatory entity and a bone detrimental effect is infl ammatory bowel disease (IBD) (33). Patients with IBD demonstrate elevated levels of IL-6, TNF α and IL1β, all of which are associated with osteoclastic activity through the activation of p38 mitogen-activated protein kinase (MAPK) pathways (33,34).…”
Section: Note: the Numerical Values Shown In The Table Represent Meanmentioning
confidence: 99%
“…A clear example of an infl ammatory entity and a bone detrimental effect is infl ammatory bowel disease (IBD) (33). Patients with IBD demonstrate elevated levels of IL-6, TNF α and IL1β, all of which are associated with osteoclastic activity through the activation of p38 mitogen-activated protein kinase (MAPK) pathways (33,34). Our previous study on older Mexico City children had shown elevated concentrations of TNF α and IL1β (5), thus a osteoclastic synergistic action is likely to be taking place as the children grow up in their polluted environment.…”
Section: Note: the Numerical Values Shown In The Table Represent Meanmentioning
confidence: 99%
“…In patients with inflammatory bowel disease bone loss is an early systemic process and occurs even before clinical disease manifests (14), and in COPD patients the prevalence of osteoporosis is high (15). In periodontitis, which is one of the most common chronic disorders in humans, both local and systemic bone loss has been described (16).…”
Section: Bone and Inflammationmentioning
confidence: 99%